Potential drivers of virulence evolution in aquaculture - David A. Kennedy; Gael Kurath; Ilana L. Brito; Maureen K. Purcell; Andrew F. Read; James R. Winton; Andrew R. Wargo (John Wiley & Sons Ltd., 2025)
Infectious diseases are economically detrimental to aquaculture, and with continued expansion and intensification of aquaculture, the importance of managing infectious diseases will likely increase in the future. Here, we use evolution of virulence theory, along with examples, to identify aquaculture practices that might lead to the evolution of increased pathogen virulence. We identify eight practices common in aquaculture that theory predicts may favor evolution toward higher pathogen virulence. Four are related to intensive aquaculture operations, and four others are related specifically to infectious disease control. Our intention is to make aquaculture managers aware of these risks, such that with increased vigilance, they might be able to detect and prevent the emergence and spread of increasingly troublesome pathogen strains in the future.